Pembuatan Media Promosi Menggunakan Desain Feed Instagram Berbasis Aplikasi Canva Pada UMKM Tropic.1996, Mojokerto - Kharinka Wahyu Irtanti; Joni Dwi Pribadi (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
Promotional media through the Instagram platform provides a space for companies to share information about their products with the aim of influencing consumers and increasing sales. UMKM Tropic.1996 has been promoting through Instagram but has not managed it effectively, resulting in unstructured product photos and an unappealing and uninformative Instagram feed. This research aims to create a feed design using the Canva application that can be used as promotional media on the Instagram account of UMKM Tropic.1996. This research adopted the action research method. Data collection methods included interviews, observations, questionnaires, and documentation. The effectiveness of the design was measured using the EPIC Rate method, which included four indicators: empathy, persuasion, impact, and communication. The research was conducted in two cycles. Based on the data obtained from the questionnaires, the average EPIC score in the first cycle indicates an effectiveness value of 4.3, while in the second cycle, the effectiveness value increased by 0.4 to 4.7 fell into the category of highly effective. In conclusion, the created Instagram feed design is deemed suitable for publication and highly effective as a promotional medium. Therefore, it is recommended that the company maintains consistency in promoting through the Instagram feed by regularly uploading content and paying attention to the day, time, caption, and hashtags when posting content to optimize the promotion.